Millimeter-wave monopole antenna with circular polarization utilizing FSS polarizer for 5G communications - Meshari D. Alanazi; Wael A.E. Ali; M.A. Abdelhady; Ahmed A. Ibrahim (Engineering Science and Technology, an International Journal)
A wide-band circularly polarized (CP) and small-size monopole antenna for millimeter wave (mm-wave) communication is presented in this paper. The monopole antenna consists of a Mickey Mouse-shaped radiator fed by a 50 Ω microstrip line on the top view of 0.203 mm RO4003C (εr = 3.5) substrate and a partial ground plane on the other side. The antenna has wide band operation extended from 24 GHz up to 38 GHz. The frequency selective surface (FSS) cells are employed to convert the linear polarization (LP) to CP. The unit cell of the FSS is composed of a dual rectangular strip with chamfered edges layout and printed on one side of a 1.575 mm RO5880 (εr = 2.2) substrate. The 3 × 3 FSS converts the illuminated LP wave to CP transmitted wave by utilizing two equally amplitude and 90° phase difference wave components. The suggested antenna is combined with the FSS cells to achieve wide-band operation from 24 GHz to 38 GHz (45.16 %). As well, the 3-dB axial ratio (AR) is extended from 27 GHz to 30.3 GHz (11.5 %) with a gain ranging from 4.2 dBi to 6.3 dB. From the outcomes, the antenna can be utilized for 5G communication.